2010
DOI: 10.1111/j.1574-695x.2010.00654.x
|View full text |Cite
|
Sign up to set email alerts
|

Shiga toxin A subunit mutant ofEscherichia coliO157:H7 releases outer membrane vesicles containing the B-pentameric complex

Abstract: Shiga toxins (STx) are secreted extracellularly through the outer membrane vesicles (OMVs) of Escherichia coli O157:H7. In an attempt to produce STxAdeficient OMVs from E. coli O157:H7, site-specific deletions of the stx1A and stx2A subunit genes were carried out. The STxA-deficient phenotype of the stx1A/stx2A mutant was confirmed by Vero cell cytotoxicity and VTEC-RPLA s assay. Western blot analyses showed that the B (STxB) subunits were present without coupling to STxA in the OMVs of the STxA-deficient muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…It has been observed that bacterial toxins components could be associated with either OMVs in Gram-negative bacteria (Chatterjee and Chaudhuri, 2011; Donato et al, 2012; Kim et al, 2010; Rompikuntal et al, 2012) or MVs in Gram-positive bacteria (Rivera et al, 2010; Thay et al, 2013). As an important potential biological weapon, Bacillus anthracis produces membrane vesicles containing biologically active toxins such as lethal factor (LF) and edema factor (EF) toxins, and serve as an important vesicular transport system for anthrax toxins and some other virulence factors (Rivera et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that bacterial toxins components could be associated with either OMVs in Gram-negative bacteria (Chatterjee and Chaudhuri, 2011; Donato et al, 2012; Kim et al, 2010; Rompikuntal et al, 2012) or MVs in Gram-positive bacteria (Rivera et al, 2010; Thay et al, 2013). As an important potential biological weapon, Bacillus anthracis produces membrane vesicles containing biologically active toxins such as lethal factor (LF) and edema factor (EF) toxins, and serve as an important vesicular transport system for anthrax toxins and some other virulence factors (Rivera et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Outer membrane vesicles (OMVs) are nano-sized spherical membrane blebs released from the outer membrane of Gram-negative bacteria during their growth (Kuehn & Kesty, 2005). As STx toxins have been known to be present within the OMVs (Kolling & Matthews, 1999;Kim et al, 2010), it is plausible that OMVs of STEC O157:H7 serve as natural vehicles for delivering STx toxins and O157-LPS to patients with D + HUS.…”
Section: Introductionmentioning
confidence: 99%
“…MsbB- and STxA-deficient mutants of EHEC O157:H7 (Sakai-DM/ stx1A / stx2A ) [11] were used as parental strains for producing mOMVs. The preparation of OMVs has been described previously [12].…”
Section: Methodsmentioning
confidence: 99%
“…Four weeks after eyedrop immunization with mOMVs, 1.5X LD 50 of wild-type EHEC O157:H7 OMVs (LD 50 0.274 mg/kg) [11] were injected intraperitoneally for the challenge experiment. Body weight changes were monitored daily for 8 days after injection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation